2002
DOI: 10.1002/mds.1195
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Occurrence of infantile epileptic seizures and childhood paroxysmal choreoathetosis in one family: Clinical, EEG, and SPECT characterization of episodic events

Abstract: The co-occurrence of infantile convulsions and childhood paroxysmal choreoathetosis (ICCA syndrome) has recently been reported in several families. The pattern of familial clustering observed is consistent with a single locus mutation which has been mapped onto the pericentromeric region of chromosome 16. We studied the main clinical, electroencephalogram (EEG), and single photon emission computed tomography (SPECT) characteristics of episodic events in a new family presenting clinical features similar to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…This provided us with further understanding of the pathophysiological mechanisms of PKD. In comparison with this, several other neuroimaging studies suggested abnormalities in other portions of the basal ganglia-thalamo-cortical circuitry in PKD, involving caudate nuclei [9], globus pallidus [12], thalamus [11,16,17]. This difference may be due to different imaging modalities, different state and relatively small sample sizes, indicating the underlying mechanisms may be rather complicated.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…This provided us with further understanding of the pathophysiological mechanisms of PKD. In comparison with this, several other neuroimaging studies suggested abnormalities in other portions of the basal ganglia-thalamo-cortical circuitry in PKD, involving caudate nuclei [9], globus pallidus [12], thalamus [11,16,17]. This difference may be due to different imaging modalities, different state and relatively small sample sizes, indicating the underlying mechanisms may be rather complicated.…”
Section: Discussionmentioning
confidence: 80%
“…Homotopic RSFC has been demonstrated to display regional variation consistent with the brain's functional hierarchy [22], and exhibit regional and hierarchical specific development trajectories across the life span [24]. Considering that the hyperactivity and perfusion abnormalities in previous studies of PKD are mostly in bilateral homotopic regions [9,12,14], we speculated that interhemispheric connectivity abnormalities could exist. Here we utilized a recently validated approach -voxel-mirrored homotopic connectivity (VMHC) [24], which directly quantified the interhemispheric RSFC between each voxel in one hemisphere and its mirrored counterpart in the opposite hemisphere, to investigate alterations of interhemispheric RSFC in PKD.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…EEG abnormalities have also been detected in a few patients with PD 19 20. The association of BIS with PD is particularly striking and has frequently been described in the same patients21 and in the same families 15 2228. Less frequently, non-infantile epileptic seizures may also associate with PD; indeed, idiopathic generalised epilepsy,29 and in particular absence epilepsy,3032 or even more complex epileptic phenotypes33 can be co-inherited with PD.…”
Section: Paroxysmal Dyskinesia and Epilepsymentioning
confidence: 95%
“…Different loci on chromosome 16 have been identified. One syndrome termed "benign infantile convulsions and paroxysmal choreoathetosis" (ICCA) is associated with seizures, suggestive of a channelopathy [94].…”
Section: Time Coursementioning
confidence: 99%